Microstructural and compositional study of metal laminated composite in Malay Keris - Musa, Mukhtarudin; Wan Yusoff, Wan Ahmad Yusmawiza; Purwanto, Hadi; Abdul Hamid, Abd. Malek; Othman, Raihan; Ani, Mohd Hanafi (American Scientific Publisher, 2017)
Keris is an exceptional Malay heritage object that has gained considerable attention. However, because its fabrication process has not been well documented, the techniques of keris making have been dying exponentially. This study aims to report the keris blade-making process and the microstructural changes that occur in the process, as well as investigate the homogeneity of elemental composition. A keris sample was obtained through the cooperation of a local keris-making workshop and the National Museum Department of Malaysia. The sample was inspected using optical microscopy (OM), field-emission scanning electron microscopy (FE-SEM), electron probe microscopy analysis (EPMA), X-ray fluorescence (XRF), and Vickers microhardness tester. The FE-SEM result shows that keris has a lamellar pearlite phase and an internal oxide layer with an average thickness of 20 m. The EPMA result shows that keris is composed mainly of Fe–2.99% C and contains an enriched layer of trace elements, such as Mn, Ni, and Si. Results lead to the conclusion that the fabrication techniques of keris contribute to the formation of a complex metal composite in its microstructure